Mercury concentrations in the tissues of blue shark (Prionace glauca) from Sagami Bay and cephalopods from East China Sea. (November 2020) - Kazama, Hitomi; Yamaguchi, Yoshitaka; Harada, Yono; Kaneko, Naoki; Mizushima, Hiroyuki; Tsuchiya, Kotaro; Nemoto, Masao; Takaku, Yuichi; Sahoo, Yu Vin; Tanaka, Miho
Abstract: The toxicity of mercury (Hg), is generally known, and around 90% of Hg exist as methylmercury (CH3 Hg + ) in marine organism. Mercury concentrates in sharks and whales, which are at the top of the food chain as predators to cephalopods. The concentrations of Hg in liver and muscle of blue shark, caught in Sagami Bay, and in digestive gland and mantles of Todarodes pacificus, Sepia madokai, and Uroteuthis edulis caught in East China Sea were measured and analyzed. The Hg concentrations in the sharks, squids, and cuttlefishes determined in this study were almost same as those in the other sea regions. In addition, the Hg concentration in the blue shark was higher in the muscle than in the liver. In S. madokai and U. edulis, Hg accumulated in the digestive gland but not in the mantle. Although the Hg concentration in the digestive gland of T. pacificus is lower than those of S. madkai and U edulis, Hg concentration in the mantle is critically higher . More than 90% of Hg is present as CH3 Hg + in muscle of blue shark and mantle of T. pacificus . This feature is explained due to amino acids with the thiol groups and chain genes in the muscle of blue shark as well as in the mantle of T. pacificus . Myosin in the mantle of T. pacificus and blue shark enhances the stability of CH3 Hg + . The amount of Hg in the digestive gland of T. pacificus could be too large to store; thus, Hg is released to the mantle, whereas the nutrients in the digestive gland of T. pacificus are supplied to other tissues. It is considered that the muscle fiber of T. pacificus is strong; therefore, large amounts of myosin levels may be present in T. pacificus than in S. madokai and U. edulis . Graphical abstract: Image 1 Highlights: Methylmercury distribution is different in the squids and cuttlefish. Large size of liver and digestive gland shows the low concentration of mercury. Large size of liver and digestive gland contains large amount of mercury. This characterization of mercury is independent on shark, squids, and cuttlefishes.